2010
DOI: 10.1159/000283687
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antigen-Stimulated Release of Tumor Necrosis Factor-Alpha in Whole Blood with Response to Chemotherapy in Patients with Pulmonary Multidrug-Resistant Tuberculosis

Abstract: Background: We have previously reported that TNF-α levels correlate to total mycobacterial burden in tuberculosis (TB) patients. Objective: To characterize the dynamics of cytokine responses in TB patients during chemotherapy to identify potential surrogate markers for effective treatment. Methods: Following induction by culture filtrate proteins in whole blood, production patterns of TNF-α, IL-10, IFN-γ and IL-12 were measured in 23 non-multidrug-resistant (MDR)-TB and 16 MDR-TB patients and in 31 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 44 publications
2
29
1
1
Order By: Relevance
“…In addition, Eum et al recently demonstrated that whole-blood TNF levels in response to culture filtrate proteins were uniquely correlated with sputum conversion in patients treated for multidrug-resistant TB (15). However, they reported a decrease in TNF in sputum-negative patients at 6 months, while we observed an increase.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In addition, Eum et al recently demonstrated that whole-blood TNF levels in response to culture filtrate proteins were uniquely correlated with sputum conversion in patients treated for multidrug-resistant TB (15). However, they reported a decrease in TNF in sputum-negative patients at 6 months, while we observed an increase.…”
Section: Discussioncontrasting
confidence: 81%
“…It has been suggested that the IFN-␥/IL-10 ratio might be used to successfully predict the development of active disease after exposure to TB (24). In addition, Eum et al recently showed that the regulation of TNF during therapy might be better than IFN-␥ in predicting sputum conversion at 6 months (15).…”
mentioning
confidence: 99%
“…IL-10 activates B and Th2 cells while inhibiting Th1 cytokine production. Activated Th2 cells secrete IL-4, which also inhibits Th1 cell activity and inactivates macrophages [10].…”
Section: Discussionmentioning
confidence: 99%
“…The largest studies that followed patients longitudinally over the course of treatment were by Eum et al [30] (38 participants with active TB, with blood samples collected after 0, 2, 6 months of treatment) and Sai et al [39] (123 participants with active TB, with blood samples collected after 0, 2, 4, 6 months of treatment). Other relatively large longitudinal studies were those by Millington et al (23 participants with active TB) [36] and Singh et al [41] (21 participants with active TB).…”
Section: Stimulated Cytokine Responsesmentioning
confidence: 99%
“…The largest study, by Eum et al, using ELISA, reported an increase in TNF-a responses with treatment [30]. Five studies using flow cytometry [31,33,35,38,44], three of which were cross-sectional [31,38,44], reported a reduction in TNF-a responses.…”
Section: Tnf-a Responsesmentioning
confidence: 99%